Aplikasi Buklet "Turun Darak" Untuk Meningkatkan Manajemen Diri Pasien Hipertensi di Desa Batu Kumbung Wilayah Kerja Puskesmas Lingsar Kabupaten Lombok Barat [Application of the “Turun Darak” Booklet to Improve Self-Management of Hypertensive Patients in Batu Kumbung Village, the Service Area of Lingsar Community Health Center, West Lombok Regency] - Ni Putu Sumartini; Theresia Avila Kurnia; Muhammad Hasby (Indonesia Berdaya, 2026)
Hypertension is one of the Non-Communicable Cardiovascular Diseases (NCDs) most commonly experienced by the public, besides Diabetes Mellitus. In hypertensive patients, the blood pressure within the vessels increases, thereby requiring the heart to pump blood harder. Although pharmacological therapy has been provided by the Primary Health Center (Puskesmas), many hypertensive patients still have uncontrolled blood pressure. This is due to inconsistency in monitoring their health and poor dietary maintenance. Consequently, hypertensive patients' self-management has not been optimally implemented. This suboptimal implementation of self-management is closely related to the low knowledge of patients regarding self-management. The objective of this community service activity was to improve the self-management of patients in Batu Kumbung Village, within the working area of Lingsar Primary Health Center, West Lombok Regency. This activity involved 10 hypertensive patients through counseling on self-management using a booklet, education on applying self-management in daily activities with a notebook, and routine blood pressure checks. The evaluation results showed that all respondents experienced an increase in their self-management scores after the intervention, reaching scores in the range of 147 to 157, all of which were categorized as "Good". Specifically, the knowledge scores of all respondents reached a minimum of 70 ("Moderate") up to 100 ("Good"), with the majority achieving a score of 100. The blood pressure (BP) in all respondents tended to decrease, although the range of this reduction was not specified whether it had reached the normal limits or not. This reduction in BP indicates the positive effect of the intervention in helping to control blood pressure. Abstrak. Hipertensi merupakan salah satu Penyakit Tidak Menular (PTM) yang menyerang system kardiovaskular yang paling banyak dialami oleh masyarakat selain Diabetes mellitus. Pada pasien hipertensi, tekanan darah di dalam pembuluh darah meningkat sehingga diperlukan pompa jantung yang lebih keras. Pemberian terapi secara farmakologi sudah diberikan oleh puskesmas namun masih banyak pasien hipertensi yang tekanan darahnya tidak terkontrol karena tidak rutin dalam mengontrol kesehatannya dan makanan yang tidak dijaga sehingga dengan demikian manajemen diri pasien hipertensi yang masih belum dilaksanakan dengan optimal. Pelaksanaan manajemen diri terkait dengan pengetahuan pasien hipertensi tentang manajemen diri yang masih rendah. Tujuan dari kegiatan pengadian masyarakat ini adalah untuk meningkatkan manajemen pasien hipertensi di Desa Batu Kumbung wilayah kerja Puskesmas Lingsar Kabupaten Lombok Barat. Kegiatan pengabmas ini dilaksanakan pada pasien hipertensi berjumlah 10 orang melalui penyuluhan tentang manajemen diri dengan menggunakan buklet, edukasi pengaplikasian manajemen diri dalam kegiatan harian dengan buku catatan, dan pemeriksaan tekanan darah secara rutin dalam kegiatan pengabmas. Hasil evaluasi menunjukkan semua responden mengalami peningkatan skor manajemen diri setelah intervensi mencapai skor di rentang 147 - 157, yang seluruhnya dikategorikan sebagai “Baik”, semua responden mencapai skor minimal 70 (Sedang) hingga 100 (Baik), dengan mayoritas mencapai skor 100, tekanan darah pada semua responden cenderung menurun meskipun masih dalam rentang yang Not specified apakah sudah normal atau tidak. Penurunan TD ini menunjukkan efek positif dari intervensi dalam mengontrol tekanan darah.